Deformation Monitoring Model of Buried Pipeline Mechanical Parts Based on the Distributed Optical Fiber Monitoring System - Bihua Shen; Xiangchao Wang; Mengya Sun; Wei Qian (Journal of Engineering)
Oil pipeline projects in China are mostly long-distance, linear projects, making pipelines vulnerable to safety problems. Consequently, pipeline monitoring is crucial for their effective maintenance. In this study, a recently developed optical fiber sensing technology was employed to monitor pipeline crossing projects and conduct tests to study the coordination deformation of buried-pipeline-soil systems using a comprehensive deformation monitoring system model based on optical fiber sensing technology developed for the test. The test realized three-dimensional monitoring of the pipeline and soil deformation when lateral displacement occurred in the soil. In addition, the feasibility of monitoring the deformation of different encapsulation types of optical fiber gratings and different sheath types of distributed optical fibers was demonstrated using this test model. The test results showed that both distributed optical fibers and fiber Bragg gratings (FBGs) could effectively reflect the strain distribution status of a pipeline during deformation monitoring. However, distributed optical fibers could detect data between two points, making them more suitable for pipeline monitoring. The FBG displacement and soil-pressure gauges could effectively monitor pipeline displacement and soil-pressure changes, thereby providing a basis for predicting the direction of slider movement during pipeline deflection and landslide monitoring. This test realized the multiparameter monitoring of pipeline deformation, pipeline displacement, and soil pressure along the pipeline, thereby providing a theoretical basis for developing prediction and warning systems for buried pipelines.